2021
DOI: 10.1371/journal.pgen.1009512
|View full text |Cite
|
Sign up to set email alerts
|

The actin nucleation factors JMY and WHAMM enable a rapid Arp2/3 complex-mediated intrinsic pathway of apoptosis

Abstract: The actin cytoskeleton is a well-known player in most vital cellular processes, but comparably little is understood about how the actin assembly machinery impacts programmed cell death pathways. In the current study, we explored roles for the human Wiskott-Aldrich Syndrome Protein (WASP) family of actin nucleation factors in DNA damage-induced apoptosis. Inactivation of each WASP-family gene revealed that two of them, JMY and WHAMM, are necessary for rapid apoptotic responses. JMY and WHAMM participate in a p5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(61 citation statements)
references
References 102 publications
(187 reference statements)
8
53
0
Order By: Relevance
“…Apoptotic F-actin-rich territories contain the JMY/WHAMM subfamily of Arp2/3-activating nucleation factors JMY, its closest homolog WHAMM, and their downstream branched actin nucleator, the Arp2/3 complex, are all required for efficient intrinsic apoptosis (King et al, 2021). Therefore, we next studied the localization of these and other actin nucleation and branching factors in relation to the F-actin-rich territories.…”
Section: Jmy Reorganization Into a Cytosolic F-actin-rich Territory I...mentioning
confidence: 99%
See 4 more Smart Citations
“…Apoptotic F-actin-rich territories contain the JMY/WHAMM subfamily of Arp2/3-activating nucleation factors JMY, its closest homolog WHAMM, and their downstream branched actin nucleator, the Arp2/3 complex, are all required for efficient intrinsic apoptosis (King et al, 2021). Therefore, we next studied the localization of these and other actin nucleation and branching factors in relation to the F-actin-rich territories.…”
Section: Jmy Reorganization Into a Cytosolic F-actin-rich Territory I...mentioning
confidence: 99%
“…Genetic inactivation of each WASP-family Arp2/3 activator previously revealed that only cells lacking JMY or WHAMM have substantial deficiencies in their intrinsic apoptosis responses (King et al, 2021). To characterize which, if any, WASP-family proteins other than JMY associate with the apoptotic F-actin territories, we treated U2OS cells with etoposide and assessed the localization of WHAMM and representatives of other subgroups within the WASP family.…”
Section: Jmy Reorganization Into a Cytosolic F-actin-rich Territory I...mentioning
confidence: 99%
See 3 more Smart Citations